2013
DOI: 10.1007/s00701-013-1929-0
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of arterial blood gas disturbances for in-hospital mortality in pediatric patients with severe traumatic brain injury

Abstract: The results of present study show that, in pediatric patients with severe head injuries, initial mixed metabolic acidosis plus respiratory acidosis and GCS are significant predictors of mortality, but other factors after adjustment for potential confounding factors had no prognostic effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Chiaretti et al [24] reported that post traumatic hypoxia and hypotension are associated with poor outcome. However, there are also studies in which hypoxia is not seen as a factor that statistically affects poor prognosis [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Chiaretti et al [24] reported that post traumatic hypoxia and hypotension are associated with poor outcome. However, there are also studies in which hypoxia is not seen as a factor that statistically affects poor prognosis [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…However, the interactions between the respiratory system and intracranial hemodynamic in brain-injured patients are more complex, and the ventilatory management is challenging. Children with severe TBI could present initial mixed metabolic acidosis plus respiratory acidosis [ 6 ] , and it is advocated the early correction of hypoxemia avoiding hypocarbia. In this scenario, the use of PEEP could improve oxygenation, but it could affect intracranial pressure.…”
Section: Discussionmentioning
confidence: 99%
“…A steep rise of pressure can affect cerebral blood flow, while secondary insults can arise from systemic factors, hypoxemia and hypotension [ 5 ]. The initial mixed metabolic acidosis plus respiratory acidosis and Glasgow Coma Scale Score (GCS) are significant predictors of mortality [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…One previous study found that initial mixed metabolic and respiratory acidosis was a significant predictor for mortality in children with severe TBI. 9 Other investigators have demonstrated that initial base deficit and lactate levels were independent prognostic factors of mortality in severe pediatric trauma patients but little is known about the utility of these values in cases of pediatric TBI. [10][11][12][13] The main aim of this study is to correlate arterial blood gas (ABG) markers and lactate levels with outcomes in children with TBI.…”
Section: Introductionmentioning
confidence: 99%